2018
DOI: 10.1029/2017jd026730
|View full text |Cite
|
Sign up to set email alerts
|

Larger Submicron Particles for Emissions With Residential Burning in Wintertime San Joaquin Valley (Fresno) than for Vehicle Combustion in Summertime South Coast Air Basin (Fontana)

Abstract: Size‐resolved composition of atmospheric aerosol particles during winter (19 December 2014 to 13 January 2015) in the San Joaquin Valley at Fresno and during summer (4 to 28 July 2015) in the Southern California Air Basin at Fontana were measured by aerosol mass spectrometer, Fourier transform infrared spectrometer, single particle soot photometer, and scanning electrical mobility sizer. The Fresno study had low‐fog and high‐fog winter conditions, and residential burning was a frequent contributor to evening e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…The average AMS nonrefractory PM 1 concentration was 7.2 ± 5.8 μg/m 3 at Fontana, with much higher concentrations on firework (14.7 ± 8.5 μg/m 3 ) days than on nonfirework (5.9 ± 2.6 μg/m 3 ) days (Figure and Table ). OM concentrations and functional group fractions in PM 1 are similar to those in PM 2.5 for Fontana (Betha et al, ), showing that most of the OM is submicron. The alkane group constituted the majority of the PM 1 OM (49%), followed by alcohol (29%), carboxylic acid (15%), amine (7%), and nonacid carbonyl (1%) groups.…”
Section: Factors Affecting the Chemical Composition Of Organic Aerosolsupporting
confidence: 58%
“…The average AMS nonrefractory PM 1 concentration was 7.2 ± 5.8 μg/m 3 at Fontana, with much higher concentrations on firework (14.7 ± 8.5 μg/m 3 ) days than on nonfirework (5.9 ± 2.6 μg/m 3 ) days (Figure and Table ). OM concentrations and functional group fractions in PM 1 are similar to those in PM 2.5 for Fontana (Betha et al, ), showing that most of the OM is submicron. The alkane group constituted the majority of the PM 1 OM (49%), followed by alcohol (29%), carboxylic acid (15%), amine (7%), and nonacid carbonyl (1%) groups.…”
Section: Factors Affecting the Chemical Composition Of Organic Aerosolsupporting
confidence: 58%
“…Refractory black carbon (rBC; Lack et al, ) concentrations and BC‐specific particle size distributions were measured using the SP2 instrument at both the Fresno and Fontana sites. While the operation of the SP2 has been previously discussed for these studies (Betha et al, ), further details are provided here and in Appendix . The SP2 measures the concentration of rBC within individual rBC‐containing particles.…”
Section: Methodsmentioning
confidence: 99%
“…The whole sampling period can be divided into four categories as previously reported Betha et al, 2018). In brief, fireworks had strong impacts on aerosol compositions from 5 to 8 July, and significant enhancements of inorganic aerosol components were observed in rBC-containing particles (Fig.…”
Section: Sp-ams Calibrationmentioning
confidence: 99%
“…Hourly average ozone data was obtained from the co-located SCAQM air monitoring station. Measurements were performed from 5 to 28 July 2015 with ambient temperature varying from 14.9 to 35.9 • C. Companion studies have shown that aerosol compositions were strongly influenced by fireworks from 4 to 8 July 2015 Betha et al, 2018). There were few clouds and little precipitation with the exception of a short storm with high rainfall and winds on 18-19 July (2-day precipitation = 3.6 cm and maximum wind speed = 10 ms −1 ).…”
Section: Sampling Location and Instrumentationsmentioning
confidence: 99%
See 1 more Smart Citation